PENERAPAN SELF-LOVE DALAM DIRI GUNA MENGURANGI TINGKAT DEPRESI PADA REMAJA - Virgita, Salsabila Ainaya; Lestari, Eka Ayu; Suratri, Sandra; Awwaliyyah, Cholilatul; Putri, Nisrina (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2024)
The development of children at the age of ’aqil baligh or adolescence is a sensitive period and has a big influence on children’s psychology. Schools have an educational role, especially in children’s psychology. with emotions that still cannot be controlled, and has a high sense of curiosity. So a teenager needs to do meditation, which is an effective way to improve physical and mental well-being. Meditation can be done by teenagers doing self-love and implementing self-love behavior in their daily lives. that meditation can help reduce stress, anxiety and depression, improve sleep quality, improve concentration and performance, and increase overall happiness and life satisfaction. Self love or loving yourself is a concept that is being widely discussed and campaigned for. Applying self-love can help maintain mental health and reduce the risk of psychological disorders. This research uses a descriptive qualitative method, namely to explore as much information as possible regarding self-love.